Análisis de la tendencia del consumo y preferencia de contenido streaming de la plataforma YouTube: de los estudiantes de la Universidad Nacional de Loja, modalidad presencial. Periodo de investigación: noviembre, 2023. - Pullaguari Armijos, Jhonny Cristian (2024)
Technological advances have significantly transformed various industries, including the audiovisual industry, highlighting the importance of understanding audience consumption trends on platforms such as YouTube. This study focuses on on-site students of the Universidad Nacional de Loja, evaluating their consumption habits and preferences on YouTube in the month of November 2023. It analyzes the consumption and preferences of streaming content, as well as the factors that influence the selection of this content. The research combined exploratory, qualitative and quantitative approaches, using the survey as a technique and the questionnaire as an instrument to collect data. The findings of this research show that 97.3% of the 407 students surveyed use YouTube, spending an average of 2 hours per day viewing mobile content, mainly entertainment content (38.9%). The most popular content includes music, tutorials, documentaries, and movies, with a marked preference for foreign content creators with 75.4% over nationals with 24.6 percentage points. This study underscores the vital role of YouTube as a source of entertainment, information and personal growth for young college students, suggesting a continued predilection for this platform to access a diverse range of content. Keywords: Consumption; Preference; Streaming; Trend; YouTube.